REVIEWS (New blackfriars, 1971)
Review in this Article ASCENT TO THE ABSOLUTE: METAPHYSICAL PAPERS AND LECTURES, by J. N. Findlay ENCYCLOPEDIA OF BIBLICAL THEOLOGY, edited by Johannes B. Bauer. THE CAMBRIDGE HISTORY OF THE BIBLE (vol. 1: From the Beginning to Jerome): edited by C. F. Evans THE EPISTLE TO RHEGINOS, by Malcoim lee peel. THE SOCIOLOGICAL INTERPRETATION OF RELIGION, by Roland Robertson. THE IDEA OF THE CITY IN ROMAN THOUGHT, by the Storoni Mazzolani.